Limbic encephalitis in children and adolescents. Issue 2 (19th October 2010) - Haberlandt, E; Bast, T; Ebner, A; Holthausen, H; Kluger, G; Kravljanac, R; Kröll-Seger, J; Kurlemann, G; Makowski, C; Rostasy, K; Tuschen-Hofstätter, E; Weber, G; et al.
Abstract : Objective: Limbic encephalitis is rare in people <18 years of age and rarely given a formal diagnosis. Design: Retrospective study on presentation and outcome of children and adolescents with the clinico-radiological syndrome of limbic encephalitis tested for specific neuronal autoantibodies (Abs) over 3.5 years. Setting: Assessment, diagnosis, treatment and follow-up at 12 neuropaediatric and neurological departments in Europe, with Abs determined in Bonn, Germany and Oxford, UK. Patients: Ten patients <18 years of age who presented with a disorder mainly affecting the limbic areas of <5 years' duration with MRI evidence of mediotemporal encephalitis (hyperintense T2/FLAIR signal, resolving over time). Results: Median age at disease onset was 14 years (range 3–17). Eight patients had defined Abs: one each with Hu or Ma1/2 Abs, four with high titre glutamic acid decarboxylase (GAD) Abs, two of whom had low voltage-gated potassium channel (VGKC) Abs and two with only low titre VGKC Abs. A tumour was only found in the patient with Hu Abs (a neuroblastoma). After a median follow-up of 15 months with corticosteroid or intravenous immunoglobulin treatment, starting after a median of 4 months, two patients recovered, eight remained impaired and one died. Conclusions: Limbic encephalitis is a disease that can occur in childhood or adolescence with many of the hallmarks of the adult disorder, suggesting that both result from similar pathogenic processes. Since most of the cases were non-paraneoplastic, as now also recognised in adults, more systematic and aggressive immunotherapies should be evaluated in order to improve outcomes.